The black book - Mann, Anthony, 1906-1967; Cummings, Robert, 1908-1990; Eagle-Lion Films, Inc.; Cinetel Films ([Los Angeles, CA] : Eagle Lion Films, 1949)
Robespierre, a powerful figure in the French Revolution and the subsequent Reign of Terror, is desperately looking for his black book, a death list of those marked by him for the guillotine and a key to help him eventually emerge as the country's dictator. He hopes that his agents will recover it, but if it falls in to the wrong hands, it would mean his political ruin and death. --
Original release title: Reign of terror.
Robert Cummings, Richard Basehart, Richard Hart, Arlene Dahl.
Director of photography, John Alton; editor, Fred Allen; music, Sol Kaplan.
In English or Spanish; with optional Spanish subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 7, 2015)
Keywords: France -- History -- Revolution, 1789-1799 -- Drama; Feature films; Historical films; Internet videos; Streaming video